Chapter 15 Invisible Suffering The Experience of Breathlessness - Carel, Havi (State University of New York Press, 2018)
This chapter presents a philosophical framework for the understanding of the experience of breathlessness. I suggest that the experience of breathlessness is total and overwhelming to the sufferer, but also largely invisible to the outsider. How does this tension play itself out for the respiratory patient? How does this tension affect respiratory medicine and clinical work? How could the first-person experience of breathlessness be better understood? Can it be usefully harnessed in the clinic? And what can a distinctively philosophical analysis offer this process? These questions are explored in the chapter, in the hope of providing a sketch of such a philosophical framework aimed at understanding this debilitating and common symptom. The structure of the chapter is as follows. It begins with an overview of breathing and the symptom of breathlessness, and how breathlessness is inter-preted in the clinic and outside it. The second section provides a phenomenological account of breathlessness, moving away from understanding it as a medical symptom to understanding it as a broader existential, social, personal, cultural, and psychological phenomenon. The final section examines how such a philosophical framework may be operationalized in a respiratory clinic, providing some examples of its possible clinical uses.